Implementation of a Stunting Monitoring System for Toddlers Using the Analytical Hierarchy Process Method in Southeast Aceh Regency - Padila Uvaira; Hafizh Al Kautsar Aidilof (Malikussaleh University, Aceh, Indonesia, 2026)
Stunting is one of the public health problems that remains a major challenge in Indonesia, including in Southeast Aceh Regency. Based on data from the Indonesian Nutritional Status Study (SSGI), the prevalence of stunting in Southeast Aceh Regency reached 34.1%, which is higher than the average prevalence in Aceh Province of 33.2%. The high rate of stunting indicates the need for more effective monitoring and handling efforts to support the growth and development of toddlers. Currently, the process of monitoring stunting in community health centers is still carried out manually, causing delays in data processing, calculation errors, and a lack of objectivity in assessing the nutritional status of toddlers. Manual recording also makes it difficult for health workers to monitor toddler development accurately and periodically. Therefore, an effective and computerized monitoring system is needed to support health services in determining stunting status more efficiently. This study aims to implement a web-based stunting monitoring system using the Analytical Hierarchy Process (AHP) method to assist health workers in determining the stunting status of toddlers more quickly, accurately, and systematically. The AHP method is applied by assigning weights to several assessment criteria, namely age, weight, height, and nutritional status. Through the weighting and calculation process, the system generates a final score used as the basis for determining whether a toddler is categorized as normal or stunted. The results of this study indicate that the application of the AHP method can support decision-making processes more objectively compared to manual methods. In addition, the developed system provides a toddler growth chart feature that helps health workers and parents monitor child development regularly. Therefore, this system is expected to improve the effectiveness and efficiency of stunting monitoring in Southeast Aceh Regency and support government efforts to reduce the prevalence of stunting.